Sustained censorship in PK (2026-03) (Pakistan) - Voidly (Voidly Global Censorship Index, 2026)
CRITICAL severity censorship detected in Pakistan. Data sourced from OONI.
Censorship Incident ID: PK-2026-0447. Severity: critical. Confidence: 85%